2013
DOI: 10.1002/ana.24014
|View full text |Cite
|
Sign up to set email alerts
|

Energy Failure

Abstract: Energy failure from mitochondrial dysfunction is proposed to be a central mechanism leading to neuronal death in a range of neurodegenerative diseases. However, energy failure has never been directly demonstrated in affected neurons in these diseases, nor has it been proved to produce degeneration in disease models. Therefore, despite considerable indirect evidence, it is not known whether energy failure truly occurs in susceptible neurons, and whether this failure is responsible for their death. This limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(72 citation statements)
references
References 131 publications
2
66
0
Order By: Relevance
“…In our studies, we showed that both mitochondrial impairment and ER stress (Ren et al, 2017) are involved in leflunomide’s toxicity and that mitochondrial impairment seems closely related to ER stress. ATP depletion, a result of impaired cellular bioenergetic, primarily leads to imbalanced mitochondrial dynamics and membrane depolarization (Pathak et al, 2013; Valero, 2014) and impacts other cellular functions such as the functions of the ER, including protein folding and calcium level regulation since they are ATP dependent. One of the plausible explanations is that the effect of bioenergetic failure and mitochondrial damage caused by leflunomide exposure could disrupt normal ER function and result in ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, we showed that both mitochondrial impairment and ER stress (Ren et al, 2017) are involved in leflunomide’s toxicity and that mitochondrial impairment seems closely related to ER stress. ATP depletion, a result of impaired cellular bioenergetic, primarily leads to imbalanced mitochondrial dynamics and membrane depolarization (Pathak et al, 2013; Valero, 2014) and impacts other cellular functions such as the functions of the ER, including protein folding and calcium level regulation since they are ATP dependent. One of the plausible explanations is that the effect of bioenergetic failure and mitochondrial damage caused by leflunomide exposure could disrupt normal ER function and result in ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Together, our findings illustrate a neuroprotective mechanism whereby RPC via neuronal Sirt1 promotes glycolytic efficiency to combat energetic stress. These results have far-reaching implications, as dysregulation of glycolysis plays a role in the pathogenesis and/or manifestation of Huntingtin’s disease, Alzheimer’s disease and Parkinson’s disease, in all of which Sirt1 has a neuroprotective role 40, 41 .…”
Section: Discussionmentioning
confidence: 99%
“…A role for mitochondrial dysfunction has emerged as a common mechanism underlying many neurological disorders [8, 12, 4143] including ASD [15, 18, 44] with specific detrimental outcomes, such as lower ATP production, increases in mitochondrial ROS, and/or metabolite-inhibition of critical steps within mitochondrial pathways [45]. In this study, we tested for bioenergetics in fibroblasts from carriers of the premutation before a significant clinical involvement was observed.…”
Section: Discussionmentioning
confidence: 99%